(untitled) (Revista Científica Estelí, 2021)
Business management is based on various theories for its application; the purpose of this article is the compilation of the theorical foundations and their application in the administrative area of companies. It is based on theoretical postulates such as the scientific theory of Frederick Taylor and the classical theory of Henry Fayol, among others. These theories are relation to business management in the micro, smalls and medium-sized enterprises (MSMEs). The relationship of the theoretical approaches with business management and their application to the management and operation of any company, regardless of its size or line of business, is shown. The methodology used consisted in the bibliographic review of the sources related with the administrative theories and business management, in books, articles of scientific journal articles and doctoral theses, consultations in the subscribed databases of the National Autonomous University of Nicaragua, Managua (UNAN-Managua), the Central American repository of the National Council of Universities (CNU) and Google Academic. The implementation of business management will allow entrepreneurs to visualize the importance of the execution of administrative management for the continuous improvement of processes, the achievement objectives, optimization of resources to achieve business development, success and sustainability.